An Investigation of Post-Merger Stress, Satisfaction and Job Leaving Intention among Employees: Evidence from the Indian Banking Sector (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present study aims to analyse and establish  association between occupational stress, job  satisfaction and job leaving intention among  employees due to merger in the Indian banking  sector. Four cases of merger involving ten public  sector banks were studied. Various statistical  tools have been used to assess the sample data  consisting of 291 employees collected from field  survey. Empirical findings indicates significant  difference in job stress, level of satisfaction and job  leaving intention across demographic variables.  With the increase in the level of stress due to  merger, the job satisfaction of employees reduces,  whereas positive relationship between the stress  and the job leaving intention due to merger was  found. The findings of the present study will be  helpful for the top management to understand  the behaviour of employees during mergers &  acquisitions and formulate such policies to help  them cope with the negative influence of merger.
Keywords: Banking; employees; merger; stress; job turnover; India; psychology